The Canadian neutral rate of interest through the lens of an overlapping-generations model - Martin Kuncl; Dmitry Matveev (Bank of Canada, 2023)
The neutral rate of interest is an important concept and communication tool for central banks. We develop a small open economy model with overlapping generations to study the determinants of the neutral real rate of interest in a small open economy. The model captures domestic factors such as population aging, declining productivity, rising government debt and inequality. Foreign factors are captured by changes in the global neutral real rate. We use the model to evaluate secular dynamics of the neutral rate in Canada from 1980 to 2018. We find that changes in both foreign and domestic factors resulted in a protracted decline in the neutral rate.
Keywords: E21; E22; E43; E50; E52; E58; F41; 330; Economic models; Interest rates; Monetary policy